2022
DOI: 10.3390/ijerph192416709
|View full text |Cite
|
Sign up to set email alerts
|

Secondary School Athletic Trainers’ Navigation of Patient Socioeconomic Status Challenges in Care: A Qualitative Study

Abstract: Secondary school ATs (SSATs) are uniquely positioned healthcare providers at an optimal public health intersection where they can provide equitable healthcare to low socioeconomic status (SES) adolescents. SSATs face similar challenges to physicians in treating low SES patients, but their strategies may be different compared to other medical professions. However, the consequences of low SES population healthcare delivery by SSATs have not been explored. SSATs were asked to share what challenges, if any, they e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Research in athletic training has highlighted that athletic trainers can have a positive outcome in reducing negative social determinants of health experiences [ 50 ]. A qualitative research study by Hernandez et al examined secondary school athletic trainers’ experiences with providing healthcare to low socioeconomic status patient populations [ 51 ]. Results were consistent with participant comments from our study, which both suggested athletic trainers are in a good position to support and advocate for low socioeconomic populations.…”
Section: Discussionmentioning
confidence: 99%
“…Research in athletic training has highlighted that athletic trainers can have a positive outcome in reducing negative social determinants of health experiences [ 50 ]. A qualitative research study by Hernandez et al examined secondary school athletic trainers’ experiences with providing healthcare to low socioeconomic status patient populations [ 51 ]. Results were consistent with participant comments from our study, which both suggested athletic trainers are in a good position to support and advocate for low socioeconomic populations.…”
Section: Discussionmentioning
confidence: 99%
“…The use of an IPA design warranted a homogenous sample of approximately 12 participants with similar lived experiences [ 10 , 11 ]. Therefore, initial recruitment began in March 2021 through invitation letters that were sent to a convenience sample of secondary school ATs.…”
Section: Methodsmentioning
confidence: 99%
“…3 Socioeconomic status influences both the healthcare available to each person, and its outcome efficacy. 8 Failure to evaluate and completely understand the impact of an individual’s social determinants of health, health literacy, and socioeconomic status decreases the ability of the healthcare professional to provide the care needed to achieve holistic health and wellbeing. 3,16 Approximately 80% of health outcomes are determined by factors beyond medical care; therefore, healthcare professionals need to have a sound understanding of how various health determinants influence overall student-athlete health.…”
mentioning
confidence: 99%
“…Although the SB-AT has the primary responsibility of providing healthcare to student-athletes, to improve the outcome efficacy of their translational healthcare interventions they should be better prepared to identify and manage the effects that social determinants of health and health literacy have on the groups that they serve. 3,8,24 To accomplish this mission, it is imperative that SB-ATs better understand the positive impact they can have on public health. 9,10 Many perceive that they were not adequately prepared to identify and intervene with lower socioeconomic status student-athletes 8 and are not familiar with how to develop and evaluate healthcare policies, and implement comprehensive translational clinical practice initiatives using traditional public health approaches.…”
mentioning
confidence: 99%
See 1 more Smart Citation